Kajian Independensi Bank Indonesia Dalam Kedudukannya Sebagai Bank Sentral Menurut Tinjauan Hukum Berdasarkan UUBI Nomor 3 Tahun 2004 Tentang Bank Indonesia - Lely Savitri Dewi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2018)
An independent state institution, Bank of Indonesia is a legal entity whose legal entity status is obtained through the enactment of Law (ie Law Number 23 of 1999 in conjunction with Bank Indonesia Regulation Number 3 of 2004 concerning Bank of Indonesia, which stipulates that Bank of Indonesia is an independent state institution both the Government and/or other parties are prohibited from interfering in the implementation of duties and authorities of Bank Indonesia (BI) violation of the prohibition of interference or obligation to refuse interference, threatened with imprisonment of at least 2 (two) years and maximum 5 (five) years and fine at least 2 (two) billion and a maximum of 5 (five) billion) The purpose of this study is to review the applicability of Bank of Indonesia law from the holder of monetary authority based on Bank Act/UUBI Number 3 of 2004 concerning Bank of Indonesia. Research method through descriptive with secondary data.